Cutting Edge: T Follicular Helper Cell Differentiation Is Defective in the Absence of Bcl6 BTB Repressor Domain Function - Nance, J. Philip (J Immunol, 2015)
T follicular helper (Tfh) cells are essential for germinal centers (GCs) and most long-term humoral immunity. Differentiation of Tfh cells depends on the transcriptional repressor B cell CLL/lymphoma 6 (Bcl6). Bcl6 mediates gene repression via the recruitment of corepressors. Currently, it is unknown how Bcl6 recruits corepressors to regulate gene expression of Tfh cells. In this article, we demonstrate, using a mutant form of Bcl6 with two BTB (bric-a-brac, tramtrack, broad-complex) mutations that abrogate corepressor binding, that the Bcl6 BTB domain is required for proper differentiation of Tfh and GC-Tfh cells in vivo. Importantly, we also observe a significant defect in GC B cell development. These results are consistent in multiple contexts, including a novel lymphocytic choriomeningitis virus nucleoprotein-specific TCR-transgenic mouse model. Taken together, these data suggest that the Bcl6 BTB domain is a key mediator of the differentiation of Tfh cells.